DSS: RECOMMENDATIONS FOR ZAKAT RECIPIENTS FOR MUSTAHIQ AT THE NATIONAL ZAKAT AMIL BODY WITH TOPSIS - Riski Arianto; Nuriadi Manurung; Akmal (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
The National Amil Zakat Agency of Asahan Regency is a religious and social institution located on Jl. Turi, Mekar Baru, Kec. West Kisaran City, Asahan Regency. The problem that is often encountered in the National Amil Zakat Agency of Asahan Regency is the selection of mustahiq which still uses the manual method, so that it still causes problems such as the length of the selection process and the occurrence of miscalculations, resulting in less accurate mustahiq selection results. In addition, the unavailability of access to information to see mustahiq who have been included in the list of zakat recipients, resulting in mustahiq who have received zakat can receive assistance more than once a year. There are several criteria in the selection and determination of mustahiq at the National Amil Zakat Agency of Asahan Regency, namely by taking into account the status of residence, income, employment status, number of dependents, and family vehicles. The distribution of zakat for mustahiq is carried out periodically, namely once a year in every holy month of Ramadan, with the number of mustahiq that have been selected by the management committee of the National Amil Zakat Agency of Asahan Regency, namely 30 mustahiq. For this reason, a system is designed that can support in making decisions on recommendations for zakat recipients for mustahiq.